Efficacy and Safety of Low-Dose Everolimus as Maintenance Immunosuppression in Cardiac Transplant Recipients - Uwe Fuchs; Armin Zittermann; Uwe Schulz; Jan F. Gummert (Journal of Transplantation)
For cardiac transplant (CTx) recipients, the recommended everolimus (EVL) dose is 0.75 mg bid or 1.5 mg bid and the target trough blood level is 3–8 μg/L. We studied a cohort of 56 CTx patients with chronic kidney disease receiving 0.75 mg bid EVL to maintain blood levels of 5–8 ug/L (designated RD group) and a cohort of 51 CTx patients with chronic kidney disease receiving 0.5 mg bid to maintain blood levels of 3–5 ug/L (designated LD group). The primary endpoint was a composite of death, rejection and premature EVL discontinuation up to 1 year after introduction of EVL. The primary endpoint was reached by 32% of patients in the LD group and by 41.1% of patients in the RD group (𝑃=0.361). Biochemical safety parameters were comparable in both groups. Our results indicate that low-dose EVL may be as effective and safe as regular dose EVL.